Entre o real e o imaginário: problematizando o currículo do curso de Licenciatura em Pedagogia em relação a gênero e sexualidade - Ferreira, Taisa de Sousa (2013)
Using perceptions established among different academic experiences related to the silence and absence imposed to some knowledge areas I discuss about the Pedagogy curriculum aiming to comprehend how discussions about gender and sexuality trespass and constitutes the pedagogue development at the State University of Feira de Santana (Bahia) beginning with the following questions: how UEFS’ Pedagogy course, in the formation process has been discussing the insertions proposed by the Federal Government and by the curricular guidelines related to sexuality and gender matters? How gender and sexuality issues are treated on curricular practices in the Pedagogy course? How professors understand the insertion of gender and sexuality subjects in UEFS’ Pedagogy course and the way they should introduce in their educative practices? This study intended to analyze the curriculo and the speech that emerge from Pedagogy course related to gender relationship, sexuality and educator formation. In this work, gender studies, and post structuralist cultural studies are mixed. We join in this trip to multiply senses, ways of researches, fights, knowledge, experiences and even voices. The research shows how are produced the debate about gender and sexuality. For that, documental analyzes and interview with six professors from Pedagogy course were made. After the analysis we noticed that the questions about gender and sexuality in Pedagogy are influenced by fields and politics of silence that make itself present in the curriculum as materiality, in the experiences of some students and professors and in powers relationships established between the professors in the course, but at the same time it point to us process, practices and subjects that enunciate and claim different ways of thinking the formation trying from the silence on to produce new meanings and senses about gender and sexuality issues. We noticed that between fissures, obliteration, words and silences, the gender and the sexuality trespass the educator formation in the investigated course. We highlight that we don’t have the intent of showing these results as definitive and unfailing, but show them as an invite to us to (re) think words, silences and the production of senses about gender e sexuality within Pedagogy course and its implication on educators’ formation.